Trajectories of CSF and plasma biomarkers across Alzheimer's disease continuum: disease staging by NF-L, p-tau181, and GFAP - Wojdała, Anna Lidia; Bellomo, Giovanni; Gaetani, Lorenzo; Toja, Andrea; Chipi, Elena; Shan, Dandan; Chiasserini, Davide; Parnetti, Lucilla (Neurobiology of disease, 2023)
CSF-to-plasma transition will open new avenues for molecular phenotyping of Alzheimer's disease (AD). Here we evaluated a panel of AD biomarkers in matched CSF and plasma samples across the AD continuum, from preclinical AD to dementia. The aims were to: 1) compare diagnostic performance of the two biofluids, 2) evaluate trajectories of the biomarkers along AD progression. We analyzed CSF and plasma Aβ42/40, p-tau181, p-tau231, t-tau, NF-L, GFAP, UCHL-1 and CSF SNAP-25 in a cohort (n = 173) of preclinical AD, MCI-AD, AD dementia, frontotemporal dementia patients, and controls. We found a significant correlation between CSF and plasma levels of Aβ42/40, p-tau181, p-tau231, NF-L, and GFAP, while no CSF-plasma correlation was observed for t-tau and UCHL-1. Next to the core CSF biomarkers (Aβ42/40, p-tau181, t-tau), those providing the best discrimination between controls and preclinical AD were CSF p-tau231 and SNAP-25 and plasma Aβ42/40, p-tau231, and GFAP. Among plasma biomarkers, we found Aβ42/Aβ40, GFAP, and p-tau231 to show the largest rate of change at the CSF biomarker-defined cut-offs for amyloidosis and tauopathy. Finally, we identified GFAP, NF-L, and p-tau181 as the biomarkers most significantly associated with disease progression in both CSF and plasma. We suggest that a well-standardized and validated panel of selected plasma markers can facilitate early AD diagnosis, even at the asymptomatic disease stage. We propose that both CSF and plasma measurement of NF-L, p-tau181, and GFAP may play a significant role in disease staging and monitoring. [Display omitted] •Aβ42/40, p-tau181, p-tau231, NF-L, and GFAP correlate in CSF and plasma.•CSF and plasma levels of UCHL-1 and t-tau do not correlate.•In plasma, Aβ42/40, p-tau231, and GFAP most effectively discriminate preclinical AD.•Both CSF and plasma NF-L, p-tau181, and GFAP are associated with AD staging.